THE EFFECT OF SUPPORTING EDUCATION IN THIRD TRIMESTER PREGNANT WOMEN TO PREPARATION FOR EXCLUSIVE BREASTFEEDING - Fritria Dwi Anggraini; Nur Zuwariah; ika mardiyanti; Fauziyatun Nisa'; Layla Imroatu Zulaikha (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
The achievement of exclusive breastfeeding is still a world problem whose target has not been achieved. The achievement rate of exclusive breastfeeding in Indonesia is still far below the national target. Therefore, breastfeeding must be prepared early so that the obstacles that are often experienced at the beginning of breastfeeding can be prevented and anticipated. The purpose of this study was to analyze the effect of providing supportive behavior education on the preparation for breastfeeding in third trimester pregnant women in the working area of ​​BPM Ulfa Surabaya. The design of this study used a Quasy experimental design with one-group pre-test-post-test design. The independent variable is supportive education about breastfeeding, while the dependent variable is the mother's behavior in the preparation of breastfeeding. The intervention was carried out 1 time each for 30 minutes. The data collection instrument used a questionnaire. The results showed an increase in the score of good readiness from 33.8% before the provision of supportive education to 69.4% after the provision of supportive education. Providing information as well as motivation (supportive education) on maternal readiness has an effect on the level of knowledge of pregnant women about breastfeeding.